URGENSI KEBIJAKAN PEMIDANAAN PEMBELI EKSPLOITASI SEKSUAL ANAK DALAM BENTUK PROSTITUSI PADA UNDANGUNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Niella Tasya Ullie; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
As the weakest and most vulnerable social beings in society, ironically, children are often put in a disadvantaged position, and become victims of a crime. One of the problems faced by children is the crime of sexual exploitation of children in the form of child prostitution. One of the reasons why child prostitution is increasing is the growing demand for the global sex market. Child sex buyers have a big hand in controlling child prostitution by creating a demand for it. Reflecting on the countries of South Korea, Philippines and Sweden which already have specific and firm national regulations in providing elements regarding the sexual exploitation of children and the punishment of buyers of child sex in the form of prostitution. This is what is needed to be accommodated in the current Child Protection Law in Indonesia by making clear, firm, and specific regulations so that it will not provide errors for all law enforcement officers in dealing with and resolving criminal cases of sexual exploitation of children in the form of child prostitution